2021
DOI: 10.21203/rs.3.rs-1017842/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Commercial Slow-Release Urea Product on in Vitro Rumen Fermentation and Ruminal Microbial Community Using RUSITEC Technique

Abstract: Background The objectives of this study were to determine the effect of commercial slow-release urea (SRU) on in vitro fermentation characteristics, nutrient digestibility, gas production, microbial protein synthesis and bacterial community using rumen simulation technique (RUSITEC). The experiment was a completely randomized design with four treatments and four replications of each treatment. Treatments were: control diet (no SRU addition), control diet plus 0.28% SRU (U28), or plus 0.56% SRU (U56), and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…is meant that carbohydrate fermentation in the rumen increased, whereas urea had no effect on microbial growth [31]. e greater NH 3 -N content from urea decomposition and readily carbohydrate fermentation from fresh cassava root supplementation may have resulted in a beneficial effect on total VFA with urea addition, creating a better Veterinary Medicine International environment for ruminal development [32,33]. Similarly, Khattab et al [34] found that adding 0, 10, and 15 g/kg urea, while Supapong and Cherdthong [9] found that adding 10 and 20 g/kg urea considerably boosted total VFA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…is meant that carbohydrate fermentation in the rumen increased, whereas urea had no effect on microbial growth [31]. e greater NH 3 -N content from urea decomposition and readily carbohydrate fermentation from fresh cassava root supplementation may have resulted in a beneficial effect on total VFA with urea addition, creating a better Veterinary Medicine International environment for ruminal development [32,33]. Similarly, Khattab et al [34] found that adding 0, 10, and 15 g/kg urea, while Supapong and Cherdthong [9] found that adding 10 and 20 g/kg urea considerably boosted total VFA synthesis.…”
Section: Discussionmentioning
confidence: 99%